Increased Levels of Serum IL-15 and TNF-β Indicate the Progression of Human Intracranial Aneurysm - Yang, Shuzhe; Liu, Qingyuan; Yang, Junhua; Wu, Jun; Wang, Shuo (Frontiers in Aging Neuroscience, 2022)
Objective: Existing evidence suggests that chronic inflammation promotes the progression of human intracranial aneurysm (IA) and many cytokines have been detected to participate in the process of inflammation. However, rare cytokines in plasma have been used as proxies for progression of IA. This study aimed to identify novel cytokines as biomarkers to predict the development of IA. Methods: Patients with unruptured intracranial aneurysms (UIAs) undergoing microsurgical clipping were prospectively recruited from January 2017 to June 2020 and were separated into two groups based on their ELAPSS score (low risk group <10, intermediate-high risk group≥10). Propensity score matching (PSM) was used to reduce imbalances in the baseline characteristics between groups. All blood samples were collected before surgery. A human serum 48-cytokines examination was performed to analyze the concentrations of serological cytokines. Clinical data and cytokines were compared between groups. Results: A total of 184 patients were enrolled in this study. The low risk group contained 77 patients and 107 patients were included in the intermediate-high risk group. Finally, there were 69 patients in each group after PSM with a matching rate of 1:1. The concentrations of 3 serum cytokines were significantly increased in intermediate-high risk patients, namely, interleukin-15 (IL-15), monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-β (TNF-β) (P < 0.05, log2|fold change| > 2). The result of receiver operator characteristic (ROC)curve revealed that TNF-β had the highest predictive accuracy, with an area under the curve (AUC) value of 0.725 (95% CI 0.639-0.811, P < 0.001) followed by IL-15 (AUC = 0.691, 95% CI 0.602-0.781, P < 0.001) and MCP-1 (AUC = 0.661, 95% CI 0.569-0.753, P = 0.001). Multivariate logistic analysis demonstrated high IL-15 [odds ratio (OR), 3.23; 95% confidence interval (CI), 1.47-7.12; P = 0.004] and high TNF-β [odds ratio (OR), 8.30; 95% confidence interval (CI), 3.25-21.25; P < 0.001] as the risk factors that correlated with intermediate-high risk of IA progression. Conclusion: UIA patients with intermediate-high growth risk exhibited increased serum levels of IL-15, MCP-1 and TNF-β. Serum IL-15, and TNF-β could serve as biomarkers to predict the progression of UIAs.